Narasi Aroma: Analisis Brand Storytelling HMNS dalam Katalog Parfum Online: Studi Kasus Produk Parfum HMNS ADDICT - Ababil Prasetyo, Ikhsan; Herman Syahputra, Achmad Irvan (Da’watuna: Journal of Communication and Islamic Broadcasting, 2026)
This study examines the construction of brand storytelling by HMNS in its online perfume catalog, focusing on the HMNS ADDICT product, and explores its interrelation with TikTok advertising narratives as part of a cross-platform storytelling strategy. Using a qualitative descriptive approach and Roland Barthes’ semiotic framework (denotation, connotation, and myth), the study analyzes textual, visual, and audiovisual representations produced by the brand. The findings show that HMNS ADDICT is positioned not merely as a fragrance but as a symbolic medium representing emotional intensity and reflective urban identity. TikTok narratives function as a pre-narrative frame that reinforces the product’s symbolic position within the brand hierarchy. The study highlights storytelling as a mechanism of meaning production that shapes product differentiation in digital marketing communication.